Strategi Pembelajaran Pendidikan Agama Kristen dalam Memperkenalkan Yesus Kepada Suku Asli Jakun - Permauli Tampubolon; Talizaro Tafonao (Institut Agama Kristen Negeri Kupang, 2021)
The purpose of writing this article is to introduce the work of Jesus Christ in the life of everyone, especially to the Jakun Native Tribe through the learning process of Christian Religious Education. One of the problems encountered by the author in this paper is that the Jakun Native Tribe still believes in aninism, customs and low knowledge / education. Based on this problem, the writer tries to make a change through humanist approaches to society as explained in this paper. The method used in this paper is a qualitative research method by examining Christian Religious Education learning strategies in introducing Jesus Christ. The analysis process used is to use a variety of literature sources both journals, books and other reliable reference materials to support the author's analysis. The results found in this study indicate that the Christian Religious Education learning strategy is very effective in applying sociological approaches, agricultural extension and culture. This can be seen in the life changes experienced by the community, namely cognitive, affective, psychomotor and spiritual changes.